Evidence that FoxP3(+) T(reg) may play a role in promoting long-term acceptance of CTA() - Bozulic, Larry D. (2011)
BACKGROUND: FoxP3(+)/CD4(+)/CD25(+) regulatory T cells (T(reg)) play an important role in maintaining peripheral tolerance and are potent suppressors of T cell activation. In the present studies we evaluated the role T(reg) might play in peripheral tolerance to composite tissue allotransplants (CTA). METHODS: Mixed allogeneic chimeric rats were prepared by pre-conditioning recipients with anti-αβ-TCR monoclonal antibody (mAb) followed by total body irradiation. Animals received T cell-depleted ACI bone marrow cells followed by anti-lymphocyte serum and FK-506. A modified osteomyocutaneous hind-limb flap composed of bone and all limb tissue components was placed at 29 days in animals with chimerism ≥ 1% on day 28. Recipients with CTA surviving ≥ 6 months were evaluated for T(reg). Skin from tolerant long-term allogeneic transplanted, syngeneic transplanted, rejected and naïve animals were immunostained with fluorochrome conjugated anti-FoxP3 and anti-CD4 mAb and visualized under a laser confocal microscope. RESULTS: Significant CD4(+)/FoxP3(+) T(reg) infiltrates were observed in tolerant donor-allograft skin samples. No graft infiltrating FoxP3(+) cells were observed in rejector, naïve, or syngeneic CTA transplanted skin. In parallel experiments, mixed leukocyte reactions assays were performed to investigate the suppressor function of T(reg) cells. Splenocytes from tolerant, rejected, and naïve rats were sorted by flow cytometry for CD4(+)/CD25(+) T cells. T(reg) demonstrated similar suppressive levels between the three groups. CONCLUSIONS: These data suggest that T(reg) may play an important role in maintenance of tolerance and promoting graft acceptance in long-term CTA acceptors and may explain the favorable outcomes observed in clinical CTA recipients.